The evolution of the endourologic management of pediatric stone disease - Smaldone, Marc C. (Medknow Publications, 2009)
In the 1980s, the advent of shock wave lithotripsy (SWL) revolutionized pediatric stone management and is currently the procedure of choice in treating most upper tract calculi <1.5 cm in children. However, with miniaturization of instruments and refinement of surgical technique the management of pediatric stone disease has undergone a dramatic evolution over the past twenty years. In a growing number of centers, ureteroscopy (URS) is now being performed in cases that previously would have been treated with SWL or percutaneous nephrolithotomy (PCNL). PCNL has replaced open surgical techniques for the treatment of large stone burdens >2 cm with efficacy and complication rates similar to the adult population. Recent results of retrospective reviews of large single institution series demonstrate stone free and complication rates with URS comparable to PCNL and SWL but concerns remain with these techniques regarding renal development and damage to the pediatric urinary tract. Randomized controlled trials comparing the efficacy of SWL and URS for upper tract stone burden are needed to reach consensus regarding the most effective primary treatment modality in children. This report provides a comprehensive review of the literature evaluating the indications, techniques, complications, and efficacy of endourologic stone management in children.